KARAKTERISTIK PEMAMPATAN TANAH RESIDU DI TPA RATAHAN - Assa, Vicky A.; Sompie, O. B.A.; Lintong, E (JURNAL ILMIAH MEDIA ENGINEERING, 2016)
AbstractSoil residues are the result of physical and chemical weathering of the rocks beneath its formation occurred over rocks came from, so there are some specific characteristics of the type of soil residues are not in accordance with the basic concepts of soil mechanics are generally prepared by the behavior of alluvial soil . The ground color is yellowish brown residue . Overview Ratahan case in landfill sites are on sloping native land , therefore the compression on the type of soil residues need more in-depth review of the determination of the parameters of consolidationThe test sample soil residue undisturbed were taken to the Laboratory of Soil Test, Department of Civil Engineering, Polytechnic of Manado for testing the water content, test weight content, test weight type, test Atterberg limits, test seepage and testing consolidation by using the tool oedometer standard. The test results were analyzed further consolidation, so that unknown behavior of soil residue compression. The results of calculations using the tool oedometer consolidation parameters in landfill Ratahan, the voltage value preconsolidation by Casagrande method is 1.20 kg / cm2 sedangan method "Strain Energy-Log Stress" or methods Senol-Saglamer was 1.50 kg / cm2. Compression index value obtained was 0.0915; and the coefficient of volume change in average yield 0.01703 cm2 / kg. Value parameter consolidation coefficient (Cv) for the type of soil residue in a landfill Ratahan can not be known because of the relationship between deformation curve and the root of the time (method Taylor), straight sections do not do not pass at least four points of each curve loading. To graph the relationship void ratio and pressure, if drawn with a logarithmic scale and a linear scale will show a different behavior. Where on the logarithmic scale graph (e log P), produces a curve that is convex making it possible to determine the preconsolidation stress, whereas the linear scale graph preconsolidation stress can not be determined. This is caused because the history of the formation of soil residues, particularly landfill Ratahan not through the deposition process and the process of consolidation as the alluvial soil.The results of the use of methods Casagrande method Senol - Saglamer for preconsolidation voltage values of 12 sites experienced an average difference of about 18.80 % . In the selection method for the determination preconsolidation stress is by using the " Strain Energy -Log Stress " ( Senol - Saglamer method , because this method has a better correlation coefficient , which is 90 % -92 % compared with the methods Casagrande 77 % -82 % ( Senol & Saglamer et.al. , 2000) .Keywords: soil residu, land fill,pre-consolidation, consolidation, Casagrande method, Senol-Saglamer method